Customer satisfaction with community pharmacy services - Milošević Georgiev, Andrijana; Neškov, Lea; Nikić, Sonja; Marinović, Valentina; Odalović, Marina; Krajnović, Dušanka (Archives of Pharmacy, 2025)
Customer satisfaction reflects the quality of pharmaceutical services and depends on various factors, such as the quality of services, pharmacists’ skills and customer’ demographic characteristics. Positive experiences strengthen customer trust and loyalty. Research into user satisfaction is an important tool for improving services. The aim of the work was the analysis of user satisfaction with pharmacy services in Serbia over the last twelve years. Annual reports on user satisfaction in pharmacies from 2013 to 2024 were analyzed. Based on key indicators, a report was prepared comparing satisfaction over the years, taking into account various factors and service quality. With the exception of 2020, public, private and health center pharmacies participated every year. The highest response rate was recorded in 2015. More than 60% of users visit a pharmacy more than five times a year, usually waiting less than five minutes. The highest level of satisfaction with the availability of medicines was recorded in 2021, while overall satisfaction with services peaked in 2022. User satisfaction has remained stable, indicating good availability and quality of pharmaceutical services. The results may contribute to further improvement in practice
Keywords: pharmacy; service; quality; customer; satisfaction